The Influence of Digital Technology, Work Ethic, Training and Integrity on Employee Performance - Tri Setiyani Darmastuti; Sudarwati Sudarwati; Istiatin Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine and analyze the influence of digital technology, work ethic, training, and integrity on employee performance at the Center for Teachers and Education Personnel (BBGTK) of Central Java Province. This research method uses a correlational study method to analyze the influence of digital technology, work ethic, training, and integrity on employee performance at the Center for Teachers and Education Personnel (BBGTK) of Central Java Province. The study was conducted during 2025 with a population of 130 employees and a sample of 100 respondents selected using a simple random sampling technique. Data collection was carried out through a Likert scale questionnaire, then analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, F tests, t tests, and coefficients of determination (R²). The results of the study indicate that digital technology has not had a significant effect on employee performance, while work ethic, training, and integrity have been shown to have a positive and significant effect on employee performance at the Center for Teachers and Education Personnel (BBGTK) of Central Java Province. Keywords:Digital Technology, Work Ethic, Training, Integrity, Performance